THE EMERGENCE OF THE GAME OF VOLLEYBALL, THE HISTORY OF ITS DEVELOPMENT IN UZBEKISTAN AND KARAKALPAKSTAN - Kamola Rakhimovna Muradova (European Science Publishing, 2024)
This article is devoted to the emergence and development of volleyball. The game of volleyball emerged from the combined techniques of basketball, handball and baseball. In 1964, volleyball was included in the program of the Olympic Games in Tokyo.
Keywords: opponent, height, game, technique, basketball, handball, kick.